Islamic economics education in Southeast Asian universities: an introduction - Barom, Mohd Nizam; Mohd Yusop, Mohd Mahyudi (Centre for Islamic Economics, International Islamic University Malaysia & International Institute of Islamic Thought, 2013)
‘Islamic Economics Education in Southeast Asian Universities’ deliberates on an important, yet relatively neglected and under-written area in Islamic economics, i.e. Islamic economics education. In view of the importance of providing the necessary guidance in the integration and Islamization process in the discipline of economics, this book starts with four important chapters that discuss conceptual issues in Islamic economics education from its philosophical foundations, curriculum structure and design, as well as the relevant issues in the process of integrating Islamic heritage (al-turath al-Islami) into economics on one hand, and the process of Islamization of mainstream economics on the other. The strive for the continuous improvement of the quality of the teaching of Islamic economics also necessitates collective efforts and the sharing of knowledge and experience among academics and institutions involve in Islamic economics education. The second part of this book is aimed at serving this purpose. These chapters can be an important point of reference for institutions currently offering or intend to offer Islamic economics program to develop and improve on the curriculum and delivery of the integration and Islamization process. Finally, the last chapter concludes this edited book by highlighting several issues critical to the success of the Islamic economics programs in view of the experiences of the different universities in the Southeast Asian region. It also proposes several solutions and future plans for the improvement of the quality of Islamic economics education. Given the scant literature available in this area, this book is an important contribution to the literature on integration and Islamization of knowledge in the discipline of economics, both at the regional and international level.